Corporate Social Responsibility dan Profitabilitas - Hans Hananto Andreas; Usil Sis Sucahyo; Delima Elisabeth (Universitas Kristen Maranatha, 2015)
This study was conducted with the aim to examine the relationbetween corporate social responsibility with corporate profitability. Corporate social responsibility would be measured by the method of opportunity cost approach by using three other variables, which was: employee relations cost,community services cost and environmental awareness cost. While the profitability of the company was measured using return on assets ratio. This study used a mining company listed on Indonesia Stock Exchange in 2010-2013 as a research sample. The final sample in this study was 26 companies. Thisstudy would be tested by using descriptive statistical analysis and correlation analysis. The result of the study indicated that corporate social responsibility variables (employee relations cost, community services cost and environmentalawareness cost) related to profitability in mining companies.Keyword: corporate social responsibility, employee relations, community services, environmental awareness, and profitability